Screening-Evaluation of Regional Investment Projects for the Provision of State Financial Support Measures - I. V. Kosorukova; O. V. Loseva; M. A. Fedotova (Финансы: теория и практика, 2024)
The object of the study is regional investment projects (RIPS). The subject of the study is a methodological toolkit for assessing the investment attractiveness of regional projects, including criteria, indicators, methods and stages of making informed decisions about government financial support measures in relation to them. The relevance of the study is due to the state’s interest in the socio-economic development of regions under the conditions of sanctions pressure and the need to ensure effective spending of budget funds allocated to regional investment projects, which requires the formation of new methodological recommendations for evaluating projects implemented within the framework of state financial support measures. The purpose of the study is to develop methodological recommendations for screening and evaluating regional investment projects in order for public authorities to make informed decisions on providing financial support. The methods of comparative analysis, classification, regulatory regulation, statistical indicators, screening and investment assessment, and the method of hierarchy analysis were used. Methodological recommendations on screening assessment of regional investment projects are proposed, within the framework of which: 1) the characteristics of RIP are identified and their classification is considered; 2) the criteria for assessing the investment attractiveness of the project and its contractor (partner) are defined: general (the purpose of the RIP, its significance, the quality of project documentation) and special (economic, budgetary, social, environmental efficiency, performance feasibility, compliance with ESG principles of doing business, business image); 3) evaluation indicators and their thresholds, the achievement of which means the expediency of investing budget funds in the project. It is concluded that in order to make a decision on the provision of state financial support to RIP, it is necessary to achieve target values by indicators corresponding to three components: “State” (customer), “Project” and “Partner (contractor). At the same time, using the hierarchy analysis method, it was found that the investment attractiveness of the contractor has the greatest importance (weight) when choosing a project. The choice of the performer is based on screening of applicants according to the specified criteria.